ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR TEKSTIL DAN GARMEN DI BEI 2019-2022 - Berlian, Dinda Trisa; Karnadi, Karnadi; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2023)
The research aims to determine the analysis of factors influencing firm value with capital structure as an intervening variable in the textile and garment sub-sector manufacturing companies listed on the Indonesia Stock Exchange (BEI). In this study, the sampling technique used is purposive sampling. Data analysis and hypothesis testing in this research utilize the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the hypothesis testing for direct effects using Smart PLS 3.0 application indicate that profitability has a positive and significant impact on capital structure. Liquidity has a positive and significant impact on the capital structure. Profitability has a positive and significant impact on firm value. Liquidity has a positive and significant impact on firm value. Capital structure has a negative but significant impact on firm value. Profitability has a negative and non-significant impact on firm value through capital structure. Liquidity has a negative and non-significant impact on firm value through capital structure.